Pembacaan Heuristik-Hermeneutik terhadap Puisi Al Ta’syirah Karya Hisyam Al-Jakh - Tita Niswatun Khasanah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2021)
This study focuses on the search for the unity of meaning contained in material objects, namely the poem Al Ta'syirah by Hisyam Al Jakh. Hisham Al Jakh is a well-known contemporary poet in Egypt. He has won several awards. The formal object of this research is heuristic and hermeneutic reading. The theory used in this research is Michael Riffaterre's semiotics. In an effort to find complete meaning in poetry, two stages of reading are needed, namely heuristic and hermeneutic reading. Heuristic reading that focuses on lexical meaning and hermeneutic reading is a contextual reading by examining the hypogram (potential and actual), models and matrices. The results of the heuristic reading of Al Ta'syirah poetry revealed that the researcher found the reading results were irregular so that it was not possible to understand what the poem meant. The potential hypogram in Al Ta'syirah's poem describes me I as a character who is brave and loves the country. The model in Al Ta'syirah poetry lies in the sentences وليس سواك أخشاه and وكل العرب إخواني بلاد العرب أوطاني. The matrix in the poem above is